How technology influences information gathering and information spreading - Iacovitti, Giovanni (Church, Communication and Culture, 2022)
Until a few decades ago, the world of information exchanges consisted mainly of interpersonal and mass communications. With the development of the global network, the Internet of Things, etc., new types of information flows have been established. Today they include the collection of huge amounts of data and their analysis with artificial intelligence techniques. Moreover, the global network is being populated by new communicating subjects equipped with artificial intelligence. These phenomena imply unprecedented problems for individuals and society, which postulate urgent regulatory interventions. In this scenario, the aim of this paper is to give a simplified but accurate idea of what is behind technological developments.